miRNA-296-3p modulates chemosensitivity of lung cancer cells by targeting CX3CR1 - Luo, Wen; Lin, Yuanlong; Meng, Shanshan; Guo, Yuening; Zhang, Jiawen; Zhang, Wei (American journal of translational research, 2016)
Lung cancer is the most common type of cancer-related death in developed countries. MicroRNAs (miRNAs) are small non-coding RNAs, which regulates gene expression in cancer. Recent studies demonstrate that the microRNA-293-3p (miR-293-3p) may play as an oncogene or a tumor suppressor. However, its expression and roles in non-small cell lung cancer (NSCLC) is not known. In this study, our purpose is to investigate the expression and roles of miR-296-3p in NSCLC. The findings indicated that miR296-3p inhibited NSCLC cell proliferation, enhance the drug resistance, and apoptosis. Data of luciferase reporter assays demonstrated that the CX3CR1 gene was a direct regulator of tumorsuppressive miR296-3p. Moreover, overexpressed CX3CR1 was confirmed in NSCLC clinical specimens. Inhibition of CX3CR1 could inhibit cancer cellular survival and increase chemotherapy sensitivity. There was a negative relationship between miR296-3p and CX3CR1 expression in NSCLC tissues. Our study elucidates that miR296-3p plays a suppressive role in NSCLC by inhibiting CX3CR1 expression.